Social attraction among Baghdad University Teaching Staff (Journal Of Educational and Psychological Researches, 2011)
During the last two decades at least, increased interest in Social attraction  variable by scientists  in psychology and sociology, to multi-dimensional and its association with psychological  and emotional variables , and what are of importance in the process of human communication , leadership, and social relations.Social psychologists interested   in social attraction also  so its relation with  social influence , political and occupational  ."Social attraction defined as "individual ability  functioned his skills in attract the group by social skills , leadership personality and social influence , so that the Community will be ascribed to the effective of the individual and supported to achieve their goals Current research aims to: . Recognition Social attraction in  the Fatality of Baghdad University. Find the difference in social attraction  according to gender variable  in  Fatality of University of Baghdad In order to achieve the goals  of the research, was building Scale (social attraction) includes  (30) items in its final form, after  delete  items which was  statistically no  significant at the level (0.05).  also distributed items of the scale on the three areas (personal appearance , emotional and , efficiency dimensions ), by covering the area and measure the phenomenon, which has developed for it . Was also selected  (100) professors, the rate of (53) females, and (47) males were selected, randomly from different College at the University of  Baghdad. as a way to extract the reliability  by(  split – half) method , for each area of the scale , as a whole, which was(0.89). (0. 82) (0.80) to the areas of scale and (0.93) for the whole scale, while the reliability  of the scale and areas, respectively (0.76) (0.80) (0.82) and (0.84) of the scale as a whole by( re-test.) method . After collecting and processing data statistically, by T- Test for Tow  independent samples showed results :There are differences social attraction  according to gender  variable, statistically significant in favor of males  value calculated T (43.7) and when compared to the indexed value was (2.750) is statistically significant at the level (0.05)    The researchers came out with several recommendations, including • The need to emphasize the importance of social attraction and its impact in the community    • Clarify what the social attraction of the Fatality Baghdad University, in selecting people for leadership positions in the field of Fatality and other areas of life.Also suggested several proposals, including: - Social skills and their relation to the social attraction  of students at Baghdad University   - Social attraction  and its relation persuasion in the Fatality of Baghdad University  - Emotional competence and its relation to the dimensions of social attractiveness (social, attraction, performance tasks).